Modeling of overloads in cyclic loading - Dindarlou, Shahram (Cranfield University, 2022)
While researchers have tried to predict mechanical response in cyclic loading, the mod- elling of overloads (monotonic loads among cycles) is still missing in the literature. This work presents a new crystal plasticity approach to predict the overload response. Even though crystal plasticity models have been available for decades, quantification of material parameters is still a matter of debate. Polycrystalline experimental results can normally be reproduced by multiple sets of parameters, raising concerns about the best parameterization to predict the grain-level response. Crystal plasticity parameters has been optimised by not only fitting experimental stress-strain curves but also independent prediction of mesoscale structures in this work. We employ a unique set of parameters with limited uncertainty to reproduce the mechanical response of FCC single- and poly- crystals in monotonic loading. We demonstrate that mesoscale parameters are material- invariant and can be used to model FCC metals with similar dislocation substructures such as for Cu, Ni and Al. Furthermore, the model is validated by comparing to experimental single- and poly-crystalline stress-strain curves and mesoscale dislocation substructure images. This work also innovates with a new optimization method to calibrate the proposed crystal plasticity model parameters. We estimated model parameters for Cu, Ni, and Al and showed that these parameters are applicable to predict stainless steel response without single crystal data. Finally, we used the model with optimised parameters to predict the overload response for Cu and NiCr alloy. The agreement with experiments for not only macroscopic re- sponse, but also mesoscale structures attributes shows robust prediction power of this work.
Keywords: Dislocation substructures; Crystal plasticity; Mesoscale material-invariant parameterization; Single crystals; Parameter optimisation; Overload model